Analisis Framing dalam Berita Kasus Pelecehan Seksual Agus Buntung di Liputan6.com - Hadi, Nadia Ramadhani; Setiawan, Hendra (Fakultas Sastra Universitas Muslim Indonesia, 2025)
This study analyzes the framing in the news reporting of a sexual harassment case committed by Agus Buntung, a person with a disability. This is done using a descriptive qualitative methodology. The focus of this study is to explain the phenomenon of how the media presents the perpetrators, victims, and related institutions in the development process of this case. Using the Miles and Huberman model, data were collected and analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the analysis show that the media uses themes that develop along with the increasing number of victims, depicting the perpetrators as smart and manipulative people even though they have physical limitations. In addition, the irony in the news is reinforced by calling the perpetrator's name with the term